2020
DOI: 10.3389/fphar.2020.01206
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxicity and Immune Dysfunction of Dendritic Cells Caused by Graphene Oxide

Abstract: Graphene, known as "black gold", has important applications in various fields. In previous studies, it has been proved that graphene oxide (GO) which is a derivative of graphene has low toxicity. However, the immunotoxicity of GO has not been fully elucidated. In this work, we used DC2.4 cell line to investigate the in vitro immunotoxicity of two types of GO, mono-layer GO (mono-GO) and multi-layer GO (multi-GO). We found that mono-GO had less effect on cell viability than multi-GO, but both mono-GO and multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 45 publications
(60 reference statements)
3
21
0
Order By: Relevance
“…Therefore, this type of multi-layer GO with more than 10 layers is more toxic than other few-layer GO studied previously in murine NIH-3T3 fibroblasts, U87 and U118 glioma cells, human lung fibroblasts cells, and even human skin HaCaT cells, up to 100 µg/ml [7][8][9][10]13]. These results are in good agreement with other studies such as that in which multi-GO showed more toxicity on cell viability than mono-GO in DC2.4 dendritic cells [11].…”
Section: Cytotoxicity Assaysupporting
confidence: 90%
See 1 more Smart Citation
“…Therefore, this type of multi-layer GO with more than 10 layers is more toxic than other few-layer GO studied previously in murine NIH-3T3 fibroblasts, U87 and U118 glioma cells, human lung fibroblasts cells, and even human skin HaCaT cells, up to 100 µg/ml [7][8][9][10]13]. These results are in good agreement with other studies such as that in which multi-GO showed more toxicity on cell viability than mono-GO in DC2.4 dendritic cells [11].…”
Section: Cytotoxicity Assaysupporting
confidence: 90%
“…In the same research line, monolayer GO has shown less effect on cell viability than multi-GO in DC2.4 dendritic cells [11]. In that study, it was demonstrated that both mono-GO and multi-GO significantly induced the generation of reactive oxygen species in the DC2.4 cells.…”
Section: Introductionmentioning
confidence: 78%
“…Single-layer GO showed low toxicity in NIH-3T3 fibroblast cells [18], and single-or two-layer GO in human lung fibroblast (HLF) cells assessed with methyl thiazolyl tetrazolium showed no cytotoxicity at 10 µg/mL after 24 h [19], nor did a few-layer GO dose of less than 20 µg/mL exhibit toxicity in human fibroblast cells [9]. In the same line of research, monolayer GO has shown a lesser effect than multi-GO on cell viability in DC2.4 dendritic cells [20]. This study showed that both mono-GO and multi-GO significantly induced the generation of reactive oxygen species in the DC2.4 cells.…”
Section: Introductionmentioning
confidence: 88%
“…To search the proteins combined with XIST, we performed the starBase database and preliminarily determined 29 candidate proteins. Among them, only 6 ones were co-expressed with XIST, including TNRC6, DGCR8, C17ORF85 (NCBP3), ZC3H7B, SFRS1 and TIA1, all of which were involved in the development and progression of diverse tumors [41][42][43][44][45][46]. Thus, we identified that these six proteins potentially interacted with XIST.…”
Section: Discussionmentioning
confidence: 97%